In azione Prove di inclusione - Giaconi, Catia (Traiettorie inclusive - Open Access, 2019)
Conceived on the occasion of the first edition of "Unimc for Inclusion", an initiative promoted by the University of Macerata, the volume intends to propose, in a single collective work, theoretical coordinates and operational trajectories applicable in plural contexts, including training whether they are educational, aggregated or residential. The paradigm of inclusion is therefore investigated on the basis of its declinations, as well as multiple perspectives of research, through a variety of thematic insights. Implementation challenges, laboratory proposals and design hypotheses that come to life in the text, offering the reader practical ideas for reflection and experimentation with an inclusive character. For these reasons, this book is particularly recommended to pedagogues, teachers and educators, both in training and in service, because in their profession they are constantly called upon to engage in "inclusion tests".